UNPACKING THE EXPERIENCE OF THE BIOSPHERE RESERVE TOURISM FROM THE ACADEMIC TOURISTS’ PERSPECTIVES: A CASE OF TASIK CHINI - Habibah Ahmad; Hamzah Jusoh; Er Ah Choy; Mushrifah Idris, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Biosphere reserves are well recognized as a ‘learning site’ for reconciling conservation, development, and learning functions. Being a learning site, the Biosphere reserves received many visitors, including academic tourists. This article aims at uncovering what academic tourists perceived as the biosphere reserve tourism of Tasik Chini Biosphere Reserve. Based on the academic tourists’ surveys conducted in 2012 and 2014, this study shows that the conservation, socio-ecological learning, and problem-solving experiences are key components of the Biosphere Reserve tourism. The context of entertainment, education, esthetic, and escapism experiences varied among academic tourists. While the academic tourists have ranked the first two components; entertainment and education at a high level of achievement, the esthetic and escapism components on the other part have been ranked at lower achievement. In bridging these contradictory achievements, the study suggests the holistic learning approach. The realistic integration of entertainment, education, esthetics, and escapism is meant to fulfil the needs of the academic tourist's needs during their visit to the Biosphere reserve sites, hence, responded to the rising of experiential tourism and experience economy.